CENTS: Cortical enhanced neonatal tissue segmentation - Shi, Feng; Shen, Dinggang; Yap, Pew-Thian; Fan, Yong; Cheng, Jie-Zhi; An, Hongyu; Wald, Lawrence L.; Gerig, Guido; Gilmore, John H.; Lin, Weili (Human brain mapping, 2011)
The acquisition of high‐quality magnetic resonance (MR) images of neonatal brains is largely hampered by their characteristically small head size and insufficient tissue contrast. As a result, subsequent image processing and analysis, especially brain tissue segmentation, are often affected. To overcome this problem, a dedicated phased array neonatal head coil is utilized to improve MR image quality by augmenting signal‐to‐noise ratio and spatial resolution without lengthening data acquisition time. In addition, a specialized hybrid atlas‐based tissue segmentation algorithm is developed for the delineation of fine structures in the acquired neonatal brain MR images. The proposed tissue segmentation method first enhances the sheet‐like cortical gray matter (GM) structures in the to‐be‐segmented neonatal image with a Hessian filter for generation of a cortical GM confidence map. A neonatal population atlas is then generated by averaging the presegmented images of a population, weighted by their cortical GM similarity with respect to the to‐be‐segmented image. Finally, the neonatal population atlas is combined with the GM confidence map, and the resulting enhanced tissue probability maps for each tissue form a hybrid atlas is used for atlas‐based segmentation. Various experiments are conducted to compare the segmentations of the proposed method with manual segmentation (on both images acquired with a dedicated phased array coil and a conventional volume coil), as well as with the segmentations of two population‐atlas‐based methods. Results show the proposed method is capable of segmenting the neonatal brain with the best accuracy, and also preserving the most structural details in the cortical regions. Hum Brain Mapp, 2011. © 2010 Wiley‐Liss, Inc.